i got a different answer that checks out, so i'm curious what i may have missed... --- Let P represent the product of roots and S the sum of roots. For clarity, let the original quadratic and conditions be defined as: y = αx^2 + βx + γ { P = 1 { S = α { βγ = -4 By using the quadratic equation, the roots of this quadratic are: [-b ± sqrt(b^2 - 4ac)] / [2a] P = ( [-β + sqrt(β^2 - 4αγ)] / [2α] )( [-β - sqrt(β^2 - 4αγ)] / [2α] ) = (-β + sqrt(β^2 - 4αγ))(-β - sqrt(β^2 - 4αγ)) / (2α)(2α) = (β^2 - sqrt(β^2 - 4αγ)^2) / 4(α)^2 = (β^2 - (β^2 - 4αγ)) / 4(α)^2 = 4αγ / 4(α)^2 P = γ/α. S = ( [-β + sqrt(β^2 - 4αγ)] / [2α] ) + ( [-β - sqrt(β^2 - 4αγ)] / [2α] ) = -2β / 2α = -β/α. So, the system of equations can be written and labelled as: (1) { γ/α = 1 <-> γ = α (2) { -β/α = α <-> β = -(α)^2 (3) { βγ = -4 <-> β = -4/γ [ {α, β,γ} in Z+ ] (2)=(3): -(α)^2 = -4/γ (1): -(α)^2 = -4/α -(α)^2 * -α = 4 (α)^3 = 4 α = 4^(1/3). α --> (2): β = -(α)^2 β = -(4^(1/3))^2 β = -(4)^(2/3). α --> (1): γ = α γ = 4^(1/3). For simplicity, let ρ = 4^(1/3). Then: α = ρ; β = -(ρ)^2; γ = ρ So, the original quadratic is: y = ρx^2 - 2(ρ^2)x + ρ. `-----------------------` Check: Condition 1: P = 1 ?= γ/α 1 ?= ρ/ρ 1 ✓= 1. Condition 2: S = α ?= -β/α ρ ?= -[-(ρ)^2] / ρ ρ ?= (ρ)^2 / ρ ρ^2 ✓= ρ^2. Condition 3: βγ ?= -4 -(ρ)^2 * ρ ?= -4 (ρ)^2 * ρ ?= 4 ρ^3 ?= 4 4^(1/3)^3 ?= 4 4^(3/3) ?= 4 4 ✓= 4.